Pedicle screw fixation combined with intermediate screw at the fracture level for treatment of thoracolumbar fractures: A meta-analysis. Issue 33 (August 2016) - Li, Kunpeng; Zhang, Wen; Liu, Dan; Xu, Hui; Geng, Wei; Luo, Dawei; Ma, Jinzhu
Abstract: Background: Use of a pedicle screw at the level of fracture, also known as an intermediate screw, has been shown to improve clinical results in managing thoracolumbar(TL) fractures, but there is a paucity of powerful evidence to support the claim. The aim of this study was to compare outcomes between pedicle screw fixation combined with intermediate screw at the fracture level and conventional pedicle screw fixation (one level above and one level below the fracture level) for thoracolumbar (TL) fractures. Methods: A meta-analysis of cohort studies was conducted between pedicle screw fixation combined with intermediate screw at the fracture level (combined screw group) and conventional pedicle screw fixation (conventional group) for the treatment of TL fractures from their inception to December 2015. An extensive search of studies was performed in PubMed, Medline, Embase, and the Cochrane library. The following outcome measures were extracted: visual analogue scale (VAS), operation time and intraoperative blood loss, Cobb angle and anterior vertebral height (AVH), and complications. Data analysis was conducted with RevMan 5.3.5. Results: From 10 relevant studies identified, 283 patients undergoing pedicle screw fixation combined with intermediate screw at the fracture level were compared with 285 conventional pedicle screw procedures. The pooled analysis showed that there was statistically significant difference in terms of postoperative Cobb angle (95% confidence interval (CI), −3.00, −0.75; P = 0.001) and AVH (95% CI, 0.04, 12.23; P = 0.05), correction loss (Cobb angle: P  < 0.0001; AVH: P  < 0.0001) and implant failure rate (95% CI, 0.06, 0.62; P = 0.006), and blood loss (W 95% CI, 2.22, 23.60; P = 0.02) between 2 groups. But in terms of other complications, there were no differences between 2 groups (95% CI, 0.23, 2.04; P = 0.50). No difference was found in operation time (95% CI, −5.36, 14.67; P = 0.36) and VAS scores (95% CI, −0.44, 0.01; P = 0.06). Conclusions: The combined screw fixation technique was associated with better reduction of the fractured vertebrae, less correction loss in the follow-up, and lower implant failure rate. Given the lack of robust clinical evidence, these findings warrant verification in large prospective registries and randomized trials with long-term follow-up.